Community Perceptions on Early Childhood Education Careers: Perspectives From Pre-Service Teachers in Zanzibar - Ali, Msellem Mohammed (Departemen Penelitian dan Pengembangan Perkumpulan Program Studi PAUD Indonesia, 2026)
This study examined community perceptions of careers in early childhood education (ECE) within preschool settings in Zanzibar, guided by Holland’s Career Choice Theory, which suggests that career decisions are influenced by individual interests, personality and environmental factors. A qualitative research approach was employed, involving 22 pre-service teachers in Zanzibar. Data were collected through semi-structured interviews and analysed using thematic analysis. The findings revealed several key perceptions, including negative stereotypes about the profession, such as societal misconceptions regarding low pay, low status, lack of proper guidance regarding career choices in ECE. The study also identified several strategies and initiatives to encourage young people to pursue careers in ECE, including raising awareness about the career, improving infrastructure to reduce overcrowded classrooms and increasing support staff in ECE schools to enhance teachers’ teaching efficiency. The study underscores the need for targeted interventions to improve the public perception and appeal of ECE as a viable and prestigious career option. It also highlights the importance of addressing challenges in the ECE teaching environment in Zanzibar, such as overcrowded classrooms, insufficient resources, and inadequate support for teachers.